'Are there Marlians in the Buhari government?' Popular music and personality cult in Nigeria. Issue 3 (3rd July 2022) - Sylvanus, Emaeyak Peter; Eze, Samson Uchenna
ABSTRACT: Today, differences in popular music genres and practices can be attributed to different peoples and cultures of the world in much the same sense as the shared and varied degrees of personality cult traditions. In this respect, Nigeria ranks amongst others with a unique and demonstrable popular music and personality cult culture. Of the available literature, none addresses the relationship between popular music and personality cult in Nigeria. This article is the first to do so. Here, we go beyond a mere analysis of the attributes of an idolised persona in, say, Naira Marley to examining both the ideological and sociological determinants––of literacy, media representation, social class, musical taste, deviancy, and demographic differences––that broadly support Nigerian popular music and personality cult practices. Through synthesising various views of the concept of personality cult with quasi-ethnographic data from some devotees of the Marlian cult, this article provides a critical intervention into how such activities as listening, imitating, and idolising are constructed forms of hero-worship in the Nigerian pop music scene.